Helping ensure respect for the SDGs under bilateral investment treaties: The case of human rights - John Gaffney (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2024)
The Sustainable Development Goals (SDGs) were established to end extreme poverty, tackle inequality and injustice and safeguard against climate change. This Perspective proposes three ways in which future BITs could be redesigned to ensure respect for SDGs and help minimize any negative impact that FDI might have on sustainable development.
Keywords: 330